Up-regulated FSTL5 inhibits invasion of hepatocellular carcinoma through the Wnt/β-catenin/YAP pathway - Zhang, Deng-Yong (Int J Clin Exp Pathol, 2017)
Patients with hepatocellular carcinoma (HCC) have a poor survival rate because of its high invasion ability. Therefore, it is necessary to elucidate the mechanisms of HCC migration and invasion. Our previous study showed that follistatin-like 5 (FSTL5), which was associated with the prognosis of HCC patients, acts as an inhibitor of HCC cell proliferation. It also promotes the transition of cell morphology from mesenchymal to epithelial, which is associated with the process of mesenchymal-to-epithelial transition. In this study, we used two HCC cell lines (SK-Hep1 and SMMC-7721) to explore the effect of FSTL5 on HCC invasion and migration. We found that up-regulated FSTL5 restrained HCC invasion and migration by transwell, wound healing, detachment, and attachment assays. Decreased expression of YAP was found upon over-expression of FSTL5, as well as inhibition of the Wnt/β-catenin signaling pathway. YAP is a downstream gene of the Wnt/β-catenin signaling pathway and plays an important role in HCC metastasis. Thus, we speculate that FSTL5 inhibits the invasion of HCC through the Wnt/β-catenin/YAP pathway. In conclusion, FSTL5 exerts an inhibitory effect on HCC metastasis and proliferation through the Wnt/β-catenin/YAP pathway and may be a target gene for anti-tumor therapy.